A Generic Matching Algorithm for Semantic Discovery - Aguilera, Unai; Abaitua, Joseba; Diaz-Labrador, Josuka; Bujan, David; de Ipina, Diego Lopez (SKG 2007 : proceedings : third International Conference on Semantics, Knowledge and Grid : Xi'an, Shan Xi, China, 29-31 October 2007, 2007)
This paper presents a generic semantic discovery algorithm, based in OWL, for UDDI registries that is not bound to any specific ontology or concepts from it. It enables to match instances and properties without specifically knowing the ontologies being matched and it enables to use all concepts contained in the request resulting in a matching closer to the user needs. Also, the generality of the proposed algorithm enables to change the ontology being used to describe an element in the registry without needing to modify the algorithm and therefore, it enables to use other OWL ontologies to describe the information stored in the registry.